Educating the deliberate professional and enhancing professional agency through peer reflection of work-integrated learning. (November 2021) - Trede, Franziska; Jackson, Denise
Educating reflexive, socially responsible and action-oriented future professionals who can contribute to a better future remains a core task of higher education. These graduate characteristics describe the deliberate professional. Within this article, we examine the value of a post-work-integrated learning peer reflection activity to foster professional agency and develop the deliberate professional in our students. Students participated in a post-work-integrated learning peer reflection activity, termed a huddle to signpost its informal yet respectful nature, and then completed a written reflection on the nature and value of this reflective experience. Findings demonstrate participants' engagement with as well as limitations towards becoming deliberate professionals. Implications for future use and further research of this peer reflection activity are offered. This study contributes new evidence that suggests that purposefully structured, dialogic and written post-work-integrated learning peer reflections are an effective approach towards developing professional agency and educating the deliberate professional.